2022
DOI: 10.1055/s-0041-1740984
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Risk Factors and Early Outcomes of Delirium in Valvular Open-Heart Surgery

Abstract: Background Compared with coronary artery bypass grafting surgery, data regarding postoperative delirium are scant in valvular open-heart surgery. Therefore, the goal of this retrospective study was to investigate the incidence, preoperative risk factors, and early outcomes of delirium in a large group of patients undergoing valvular open-heart surgery. Methods In 13,229 patients with isolated valvular or combined valvular and bypass surgery, the incidence of postoperative delirium was assessed until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This difference may be attributable to higher doses of dopamine and longer use duration in Yilmaz’s study. In addition, delirium was very common after cardiac surgery ( 24 ). Therefore, further studies are required to evaluate the relationship between low-dose dopamine and clinical effects and its internal mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be attributable to higher doses of dopamine and longer use duration in Yilmaz’s study. In addition, delirium was very common after cardiac surgery ( 24 ). Therefore, further studies are required to evaluate the relationship between low-dose dopamine and clinical effects and its internal mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors also identified preoperative anemia as a risk factor for delirium after non-cardiac as well as after cardiac surgery. [29–32]…”
Section: Discussionmentioning
confidence: 99%
“…Other authors also identified preoperative anemia as a risk factor for delirium after non-cardiac as well as after cardiac surgery. [29][30][31][32] Recently, consensus recommendations from an international conference on the role of perioperative cerebral NIRS were published. [33] With regard to preoperative values, the authors state that they recommend the use of preoperative cerebral oximetry to identify patients at increased risk of adverse outcomes after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Additionally, POD manifests more intensely in elderly patients compared to younger cohorts, complicating post-surgical family communications and intensifying already strained relationships between healthcare providers and patients. The incidence of POD varies significantly across surgical procedures (ranging from 4.1% to 67%), [ 5 , 6 ] underscoring its complex etiology. Identified risk factors include preoperative anxiety, [ 7 ] smoking history, [ 8 ] hypertension, [ 9 ] the use of sleeping pills, open surgical techniques, [ 10 ] as well as heightened levels of postoperative pain and opioid consumption.…”
Section: Introductionmentioning
confidence: 99%